Is education possible in the metaverse especially in Indonesia? - Nurul Hasannah; Aghniya Faza Afina; Popi Nuraeni; Angga Hadiapurwa (Himpunan Pengembang Kurikulum Indonesia, 2024)
Metaverse in education is one of the innovations in learning media based on three-dimensional virtual space technology whose implementation is currently being widely used. This article aims to determine the development and use of metaverses in education by reviewing the literature on using metaverses in learning. This research uses a systematic literature review method, namely reviewing literature in the form of relevant books and articles. Data collection was summarized from international journal articles, accredited and non-accredited national journals, proceedings, theses, and theses. From the results of the literature study, it is known that the metaverse in the world of education began to be effectively used during the Covid-19 pandemic, where the metaverse was able to overcome the limitations of distance and time to enter class and the acceleration of metaverse technology in the world of education has been seen with the existence of digital-based learning media applications: Augmented reality and virtual reality. With the virtual world concept, online learning can be done more interactively and innovatively. This flexible learning is an interesting and innovative learning method concept. Abstrak Metaverse dalam dunia pendidikan merupakan salah satu inovasi media pembelajaran berbasis teknologi ruang virtual tiga dimensi yang saat ini implementasinya mulai banyak digunakan. Artikel ini bertujuan untuk mengetahui perkembangan dan penggunaan metaverse dalam dunia pendidikan dengan meninjau literatur yang berkaitan dengan penggunaan metaverse dalam pembelajaran. Penelitian ini menggunakan metode systematic literature review, yaitu meninjau literatur, berupa buku dan artikel yang relevan. Pengumpulan data dirangkum dari artikel jurnal internasional, jurnal nasional terakreditasi dan non akreditasi, prosiding, tesis dan skripsi. Dari hasil literature review, diketahui bahwa metaverse dalam dunia pendidikan mulai efektif digunakan pada saat terjadinya pandemik COVID-19, dimana metaverse mampu untuk mengatasi keterbatasan jarak dan waktu untuk masuk kelas dan akselerasi teknologi metaverse di dunia pendidikan sudah terlihat dengan adanya aplikasi media pembelajaran digital berbasis augmented reality dan virtual reality. Dengan konsep dunia virtual, pembelajaran secara online dapat dilakukan dengan lebih interaktif dan inovatif, seperti terbentuknya ruang kelas meskipun tidak bertemu secara langsung, praktikum secara virtual, dan lain-lain. Pembelajaran yang bersifat fleksibel ini menjadi konsep metode pembelajaran menarik dan inovatif Kata Kunci: metaverse; perkembangan metaverse; pendidikan